Propedeutyka wiedzy o mediacji w szkole. Kompetencje mediacyjne nauczyciela i ucznia - Łacina-Łanowski, Artur (Studia Edukacyjne, 2021)
The changes attendant to the social and political system had an impact on Polish schools. Due to these changes, teachers need to handle such challenges as a tarnished image of schools and teachers, hyperactive parents, excessively direct students’ behaviors and social problems, especially school violence; all of them are greatly deconstructive for the school system. An effective coping method is not only teachers’ lifelong development, especially in terms of social competencies, but also establishing students’ competencies from the very early stage of education. To achieve that, teachers should create a suitable atmosphere in the area of interpersonal relations, which can be achieved by creating a very effective internal communication system. A constructive dialog at school may importantly influence not only the development of students’ mediation skills, but also the mitigation of conflicts and tensions. This is also a key component of facilitating the mediation process.